3‐Methylcholanthrene/Aryl‐Hydrocarbon Receptor‐Mediated Hypertension Through eNOS Inactivation. Issue 5 (10th August 2016) - Chang, Chih‐Cheng; Hsu, Yung‐Ho; Chou, Hsiu‐Chu; Lee, Yuan‐Chii G.; Juan, Shu‐Hui
Abstract : Endothelial nitric oxide synthase (eNOS) modulates vascular blood pressure and is predominantly expressed in endothelial cells and activated through the protein kinase B (Akt/PKB)‐dependent pathway. We previously reported that 3‐methylcholanthrene (3MC) activates the aryl hydrocarbon receptor (AhR) and reduces PI3K/Akt phosphorylation. This study investigated the mechanism underlying the downregulatory effects of 3‐MC on nitric oxide (NO) production occurring through the AhR/RhoA/Akt‐mediated mechanism. The mechanism underlying the effects of 3‐MC on eNOS activity and blood pressure was examined in vitro and in vivo through genetic and pharmacological approaches. Results indicated that 3‐MC modified heat shock protein 90 (HSP90), caveolin‐1, dynein, and eNOS mRNA and protein expression through the AhR/RhoA‐dependent mechanism in mouse cerebral vascular endothelial cells (MCVECs) and that 3‐MC reduced eNOS phosphorylation through the AhR/RhoA‐mediated inactivation of Akt1. The upregulation of dynein expression was associated with decreased eNOS dimer formation (eNOS dimer; an activated form of the enzyme). Coimmunoprecipitation assay results indicated that 3‐MC significantly reduced the interaction between eNOS and its regulatory proteins, including Akt1 and HSP90, but increased the interaction between eNOS and caveolin‐1. Immunofluorescence and Western blot analysis revealed that 3‐MC reduced the amount of membrane‐bound activated eNOS, and a modified Griess assay revealed that 3‐MC concomitantly reduced NO production. However, simvastatin reduced 3‐MC‐mediated murine hypertension. Our study results indicate that AhR, RhoA, and eNOS have major roles in blood pressure regulation. Statin intervention might provide a potential therapeutic approach for reducing hypertension caused by 3‐MC. J. Cell. Physiol. 232: 1020–1029, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Our study is the first to report that the AhR ligand 3‐MC inactivated eNOS associated with downregulated HSP90 and upregulated caveolin‐1 and dynein expression through AhR/RhoA‐mediated PI3K/Akt inactivation, leading to hypertension in mice. The blockade of AhR and RhoA by using siAhR, DNRhoA, or statins reversed the inhibitory effects of 3‐MC on eNOS by correcting the alterations of eNOS regulatory proteins.